Lecturer Resilience as a Key Factor in Enhancing Academic Performance: The Influence of Personal Factors, Work Environment, and Institutional Support on Lecturer Productivity in Health Higher Education Institutions - Isnainy, Usastiawaty Cik Ayu Saadiah; Zainaro, M. Arifki (Universitas Aisyah Pringsewu, 2024)
This article discusses resilience as a key factor in enhancing academic performance among lecturers in higher education institutions. In facing increasing professional demands, lecturers often experience pressures that impact their physical and mental well-being. Resilience, defined as the ability to recover and positively adapt to stress, has been shown to contribute to stable and high-quality performance. This study aims to explore the relationship between lecturers' resilience levels and their performance in teaching, research, and clinical service. Using a quantitative approach with data analysis conducted through Structural Equation Modeling (SEM), the research involved 200 lecturers from various health higher education institutions. The results indicate a significant positive relationship between resilience and lecturer performance, with a regression coefficient of 0.613. Factors influencing lecturers' resilience include social support, a conducive work environment, and institutional support. These findings highlight the importance of educational institutions designing support programs that can strengthen lecturers' resilience, thereby enhancing their productivity and well-being. Thus, this article provides insights into how resilience can affect lecturers' performance and emphasizes the need to create supportive environments to improve educational quality. Efforts to bolster lecturers' resilience are expected to contribute to their professional development and career sustainability in the academic world.